A Systematic Review of Supportive Therapy Effect on Quality of Life in Cancer Patients - Suharyono Suharyono; Suhendra Agung Wibowo; Ira Purnamasari; Tintin Sukartini (Universitas Airlangga, 2020)
Introduction: Supportive therapy is considered an important element in the treatment of cancer patients which is often associated with efforts to overcome life-threatening problems. However, the application of this intervention in clinical practice has not yet been fully carried out. This systematic review summarizes the evidence regarding the effect of supportive therapy in improving the quality of life (QoL) of cancer patients.Methods: The review was performed according to PRISMA guidelines. We searched four electronic databases to identify studies comparing patients who received specific protocol interventions with the control group. The keywords used are